Evolution of the Gut Microbiota and Its Fermentation Characteristics of Ningxiang Pigs at the Young Stage - Hao Li; Longteng Ma; Zhiqing Li; Jie Yin; Bie Tan; Jiashun Chen; Qian Jiang; Xiaokang Ma (Animals, 2021)
The current study aimed to investigate the evolution of gut microbiota and its influencing factors for NXP in youth. The results showed that Shannon index increased from d 21 to d 28 whereas the ACE index increased from d 21 until d 60. Firmicutes, mainly Lactobacillus dominated on d 21. The Bacteroides and Spirochetes showed highest relative abundance on d 28. Fiber-degrading bacteria, mainly Prevotellaceae, Lachnospiraceae, Ruminococcaceae, Muribaculaceae, and Oscillospiraceae_UCG−002, dominated the microbial communities at d 28 and d 35. The microbial communities at d 60 and d 75 contained more Clostridium_sensu_stricto_1, Terrisporobacter and Oscillospiraceae_UCG−005 than other ages, which had significantly positive correlations with acetate and total SCFAs concentration. In conclusion, the evolution of gut microbiota was mainly adapted to the change of dietary factors during NXP growth. The response of fiber-degrading bacteria at different stages may help NXP better adapt to plant-derived feeds.